2021
DOI: 10.1002/mabi.202100102
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Protein‐Loaded pH‐Stable Polymersomes: First Step toward Protein Targeted Therapeutics

Abstract: Synthetic platforms for mimicking artificial organelles or for designing multivalent protein therapeutics for targeting cell surface, extracellular matrix, and tissues are in the focus of this study. Furthermore, the availability of a multi‐functionalized and stimuli‐responsive carrier system is required that can be used for sequential in situ and/or post loading of different proteins combined with post‐functionalization steps. Until now, polymersomes exhibit excellent key characteristics to fulfill those requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 73 publications
2
21
0
Order By: Relevance
“…[ 7,8 ] Furthermore, functional groups sensitive to glucose/sugar concentration, [ 9,10 ] redox levels [ 11 ] or irradiation can also be incorporated onto the BCPs. [ 12,13 ] Surface functionalization of the polymersomes [ 14 ] allows selective targeting of cells, thereby promoting the use of polymersomes as drug‐delivery systems. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 7,8 ] Furthermore, functional groups sensitive to glucose/sugar concentration, [ 9,10 ] redox levels [ 11 ] or irradiation can also be incorporated onto the BCPs. [ 12,13 ] Surface functionalization of the polymersomes [ 14 ] allows selective targeting of cells, thereby promoting the use of polymersomes as drug‐delivery systems. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…Covalent attachment of molecules at the compartment surface involves different chemical approaches. For example, strategies based on Cu 2+ -free click chemistry are achieved by: (i) azide–alkyne cycloaddition [ 106 , 107 , 108 , 109 , 110 ], (ii) maleimide and thiol-ene [ 111 , 112 , 113 , 114 , 115 ], and (iii) amine coupling [ 114 , 116 , 117 , 118 ]. Using a combination of strain-promoted azide–alkyne cycloaddition (SPAAC) and thiol-ene reactions, the surface modification of poly(2-methyl-2-oxazoline)- block -poly(dimethylsiloxane) (PMOXA- b -PDMS) polymersomes served to immobilize polymersomes on surfaces [ 111 , 112 , 119 ].…”
Section: Generation Of Synthetic Compartmentsmentioning
confidence: 99%
“…The pH-responsive and crosslinked Psomes have previously been used to incorporate active biomacromolecules, especially enzymes, to design artificial organelles. They are versatile, chemically and physically stable, membrane permeability for different bio(macro)molecules, and capable of regulating enzyme activity through the pH-sensitive membrane permeability, 9,10,38,[43][44][45][46][47][48][49][50][51][52] such as crosslinking and permeabilizing of pH-responsive GOx/CAT-Psomes by S. Liu group 50 . The preparation process and characterization methods of artificial organelles GOx-Psomes A and Urease-Psomes B are based on our previous report, 38,43,47 at which the collapsed membrane state of pH-responsive Psomes does not allow the feeding of lumen-located enzyme in Psomes with any low-molecular weight substrate or intermediates (e.g.…”
Section: Construction Of Artificial Organelles: Gox-psomes a And Urea...mentioning
confidence: 99%
“…Asymmetrical flow-field flow fractionation with light scattering detection (AF4-LS) as a powerful method to confirm molar mass, size, and conformational properties of Empty-Psomes and Enzyme-Psomes has been well established in our group. 9,10,38,[44][45][46][47][48] Previous studies on GOx-Psomes A and Urease-Psomes B in PBS buffer at pH 7.0 and 5.0 by AF4-LS have been presented. 38 These results demonstrated that the scaling parameters ν of GOx-Psomes A and Urease-Psomes B are relatively close to 0.33, implying Enzyme-Psomes with a regular spherical morphology at different conditions.…”
Section: Construction Of Artificial Organelles: Gox-psomes a And Urea...mentioning
confidence: 99%